Det koster at være lille. Grønlands hjemtagelser 1980 til 1993 og smådriftsulemper - Lars Lund (Copenhagen Business School (CBS), Department of Economics, 2018)
– After home rule in 1979 Greenland gradually takes over expenditure of general government from Denmark during the 1980ies. Step by step Denmark gives a subsidy to Greenland covering what were the Danish expenditures. Nearly the entire subsidy comes in four lumps, 1980, 1985, 1987 and 1992. Subsequently the subsidies have been regulated according to the increase in costs for the Danish general government in providing services. Supposing government expenditures being a constant fraction of GDP, we calculate what would have been the hypothetical Danish expenditures to the four areas and then compare these to the actual Greenlandic expenditures in 1994 and 2014. Actual expenditures are much higher than the projected Danish ones. Especially this is true for general public services and education where the level is more than twice the projection. The article's point of view is that a large part of the overshooting is due to small scale diseconomies.
hdl:10398/9677
Keywords: E62; O52; R50; 330; Greenland; Governemt Expenditure; Small Scale Disadvantages